An Analysis Of Students Problem In Learning Speaking At MA Arrohman Sumoyono Jombang - Khudriyah Khudriyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
Teaching speaking needs high effort since it is difficult subject, the learners have mastery all components of the language such as comprehension, grammar, vocabulary, pronunciation and fluency. This study is aimed to know what the students error in learning speaking and what are the causes. This study is qualitative descriptive, with case study approach. To collect data the researcher used observation, and questionnaire, then the data was analyzed using model of Miles & Huberman. The result of the study was the students error in learning speaking English were (1) speech errors with types of silent pause, filled, repeat, un-retraced, retraced, correction, stutters, and slip tongue (2) grammatical error about omission of bound morpheme, omission of auxiliary, preposition, and wrong in words selection (3) pronunciation error, and code switching. The factor caused the error is knowledge factor, such as having no language aspect, lack of vocabulary, grammar, pronunciation, and never practice; affective factor or students low attitude and motivation, and personal factor was high of shyness, and afraid of being laughed.